Transparansi Seleksi CPNS Di Indonesia: Realita, Tantangan, Dan Implikasinya – Kajian Literatur: Tinjauan rekrutmen CPNS di Indonesia dari riset terdahulu - Novia Rosa; Aditiawarman; Rina Yuliani; Mardianti; Zulham; Zul Fahmi (Universitas Mbojo Bima, 2025)
This study aims to examine the implementation of the principle of transparency in the recruitment process of Civil Servant Candidates (CPNS) across various regions in Indonesia, using a Systematic Literature Review (SLR) approach. The SLR method is employed to collect, select, and analyze a range of academic sources and relevant documents from journal databases and reputable online repositories. The stages of this research include identifying keywords, searching for articles based on inclusion and exclusion criteria, assessing the quality of the sources, and synthesizing the findings to identify key patterns and insights regarding indicators and obstacles in the application of transparency. The findings reveal that the implementation of transparency principles is generally in accordance with regulations and contributes positively to participants’ perceptions of the selection process. However, several challenges remain, such as limited access to information and complex bureaucratic procedures, which require further attention. Optimal implementation of transparency is believed to enhance public trust and improve the quality of public services. This study recommends the need to strengthen public outreach and the utilization of technology, such as digital platforms and official websites, as effective channels for delivering comprehensive and up-to-date information, as well as for providing accessible registration forms for participants from diverse social backgrounds.